Blended Learning for Augmented Reality to Increase Student Competitiveness the Filling Subject Toward Making Indonesia 4.0 - Kusdiyanti, Heny; Nurruddin Zanky, Mokhammad; Prasetyo Wati, Andy (KnE Social Sciences, 2020)
Human resource development can be done by various step such as improvement of quality education especially model and learning methode. The Filling Subject is the important thing to increase the competitiveness of student at Vacational Hight School especialy Administration Department. Today teachers just have conventional methode to deliver their knowledge. Therefor student hard to understand the knowledge that delivered by teacher. Indonesia’s government have launced policy that called Making Indonesia 4.0 againts this global era. Blended Learning is one of the effective methode to deliver knowledge to students because this methode make student understand easily. Augmented Reality is one of the technology that can be collaborated with Blended Learning. This study purposed to create modul based on Augmented Reality as Blended Learning implementation in Filling Subject at Vocational Hight School Malang Regency. The study method modified from research and development models that called 4-D (define, design, develop, and disseminate). This study using quantitative dan qualitative data that collected from questionnaire. The questionnaire will be given to the material expert, the media expert and the students in Administration Departement at Vacational Hight School Malang Regency. The result of this study are: 1) product has been validate by the material expert of Filling Subject; 2) product has been validate by the media expert of Augmented Reality; 3) product has been implemented with Blended Learning Model to the Administration Departement Student in the Vacational Hight School Malang Recency and succeed to increase their competence in the Filling Subject. The implementation of Blended Learning for Augmented Reality suggested to be implemented in the other learning subject because it is very effective to increase the student competitiveness and make learning that done by teacher more easily. Keywords: Augmented Reality, Blended Learning, Filling Subject, Module, Vacational Hight School.